Implementation of super H-antimagic total graph on establishing stream cipher - Antonius Cahya Prihandoko; D. Dafik; Ika Hesti Agustin (Indonesian Combinatorial Society (InaCombS), 2019)
This paper is aimed to study the use of super (a, d)-H antimagic total graph on generating encryption keys that can be used to establish a stream cipher. Methodology to achieve this goal was undertaken in three steps. First of all the existence of super (a, d)-H-antimagic total labeling was proven. At the second step, the algorithm for utilizing the labeling to construct a key stream was developed, and finally, the mechanism for applying the key to establish a stream cipher was constructed. As the result, according to the security analysis, it can be shown that the developed cryptographic system achieve a good security.